Correlation between functional health literacy and self-efficacy in people with type 2 Diabetes Mellitus: ross-sectional tudy - Medina, Luis Angel Cendejas (2021)
To analyze the correlation between functional health literacy (FHL) and self-efficacy (SE) in people with type 2 Diabetes Mellitus. Cross-sectional study was conducted among September and October 2019, with 196 people with type 2 diabetes. Data were collected using the Functional Literacy in Health instrument (B-TOFHLA) and the Diabetes Management Self-Efficacy Scale for Patients with Type 2 Diabetes Mellitus (DMSES). Bivariate analysis was used to verify the relationship among the constructs. Most diabetics showed an average B-TOFHLA score of 74.75, considered adequate, and self-efficacy of 4.07, high. The association between SE and FHL in the bivariate analysis found no statistical significance (p > .05), in the same sense as the B-TOFHLA score and the DMSES domains (p > .05). Constructs were not related to each other in terms of skills arising from judgments and decisions with motivational confidence by the investigated audience.